Desarrollo de un sistema de control de procesos del personal docente por competencia de la unidad educativa antares - Cando Quimi, Daniel (2009)
The Teaching Staff Processes Control by competences of the Unidad Educativa Antares is very important to develop the teachers’ strategic and operative capacity to evaluate and guide the basic management processes in the high school using the Balanced Scored Card methodology. This project consists in a system which controls the teaching and learning evaluation of teachers from the institution orientated to their students, in order to get skill identification and content according to each teacher skills. In the first chapter, we will find a general description of the Institution. In the second chapter, we will find the methodology of management processes in which we will detail all the elements that interact in each of the processes of the institution through process maps and flow charts (SIPOC). The third chapter has the system and how to interact with it. It was developed using programming techniques as JSP and My SQL Server Database. The forth chapter includes the Database multivariate analysis to conclude with recommendations about the processes in the last chapter.